2002
DOI: 10.1152/ajpcell.00314.2001
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB induced by IL-1β inhibits elastin transcription and myofibroblast phenotype

Abstract: . NF-B induced by IL-1␤ inhibits elastin transcription and myofibroblast phenotype. Am J Physiol Cell Physiol 283: C58-C65, 2002; 10.1152/ ajpcell.00314.2001.-Interleukin (IL)-1␤ released after lung injury regulates the production of extracellular matrix components. We found that IL-1␤ treatment reduced the rate of elastin gene transcription by 74% in neonatal rat lung fibroblasts. Deletion analysis of the rat elastin promoter detected a cis-acting element located at Ϫ118 to Ϫ102 bp that strongly bound Sp1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
58
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 34 publications
4
58
0
1
Order By: Relevance
“…Alternatively, NFB could reduce Sp1 binding to DNA through protein-protein interactions that don't directly involve DNA contact points. Interaction of p65 and Sp1 have been demonstrated in co-immunoprecipitation studies previously (72). If this is the correct mechanism, it would imply selectivity for certain Sp1-binding elements, because Sp1 binding to the downstream element was unaffected by TNF-␣ treatment.…”
Section: Figmentioning
confidence: 82%
“…Alternatively, NFB could reduce Sp1 binding to DNA through protein-protein interactions that don't directly involve DNA contact points. Interaction of p65 and Sp1 have been demonstrated in co-immunoprecipitation studies previously (72). If this is the correct mechanism, it would imply selectivity for certain Sp1-binding elements, because Sp1 binding to the downstream element was unaffected by TNF-␣ treatment.…”
Section: Figmentioning
confidence: 82%
“…Activation of NFB induced by interleukin-1␤ decreased elastin promoter activity and elastin mRNA level. 10 NFB may also affect elastin synthesis indirectly through decreased tumor necrosis factor ␣ expression. Tumor necrosis factor ␣ is regulated by NFB and has been found to markedly suppress the elastin mRNA level and transcriptional activity of the elastin gene in cultured human skin fibroblasts and rat aortic vascular smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Furthermore, recent studies have demonstrated that NFB inhibits transcription of the elastin and collagen genes, leading to suppression of their synthesis. 10,11 In contrast, members of the ets family, including MMP-1, MMP-2, and MMP-9, also play important roles in regulating gene expression in response to multiple developmental and mitogenic signals. [12][13][14] From this viewpoint, we used chimeric decoy oligodeoxynucleotides (ODNs) to inhibit both NFB and ets simultaneously, leading to the inhibition of a wide variety of MMPs, including MMP-1, MMP-2, MMP-3, and MMP-9, which play a pivotal role in human AAA.…”
mentioning
confidence: 99%
“…Other positive-acting ELN promoter elements directly bind transactivating factors, such as the nuclear factor-1 binding site at approximately Ϫ400 of the ELN gene (5). Functional elements that repress elastin expression on exposure to basic fibroblast growth factor (bFGF) (2,3,27), interleukin (IL)-1␤ (14,15), and tumor necrosis factor-␣ (TNF-␣) (11) have been defined. Studies in transgenic mice reported tissue-specific activity of a transgene containing 5.2 kb of 5Ј-flanking sequence, although comparisons between expression patterns of the transgene and the endogenous gene were not made (9,13,17,26).…”
mentioning
confidence: 99%